Smart Contracts: Myths and Implications for Economics and Financial Regulation - William Lehr (International Telecommunications Society (ITS), 2022)
This paper seeks to situate an understanding of the long-term implications of Smart Contract (SC) technologies as a cluster of technologies that together with AI (shorthand for software applications) and 5G (shorthand for networked ICTs) will prove important for enabling a future wherein any task may be automated. Although the "any task can be automated" future is far off and AI, 5G, and SC technologies are still evolving rapidly, this paper argues for timely consideration of the policy implications for SCs. Like those other technologies and to a perhaps even greater extent, SC technologies (which include cryptocurrencies, blockchain, and smart contracts as distinct elements) have been the focus of excessive hype that has given rise in the academic and mass media press to misconceptions about what is important about SCs that this paper seeks to identify and dispel. In an effort to start to understand the challenges and likely trajectory for SC regulation, this paper focuses on FINTECH and the policy challenges that are emerging there related to SCs. The overall conclusion is that lots more needs to be done, and while it is clear that SCs will play an important role in FINTECH's future and the regulation of that future will require significant focused research attention, it is unclear how useful such research will be as a template for addressing the challenges that will emerge as SCs migrate to other sectors where the economic implications are expected to be much larger. The paper concludes with speculations about where key trends in SC technologies seem to be going.
Keywords: D86; K12; L14; O3; D51; D52; D4; G2; P00; P48; 330; Blockchain; 5G; Smart Contracts; Digital Markets; Cryptocurrencies; Regulation; FINTECH